2014
DOI: 10.3233/jae-141773
|View full text |Cite
|
Sign up to set email alerts
|

Optimization design of low-speed surface-mounted PMSM for pumping unit

Abstract: Efficiency and torque ripple are usually especially concerned during the working process of permanent magnet synchronous motor (PMSM). The loss and cogging torque generated during the working process of PMSM are analyzed. A low-speed surface-mounted PMSM used for direct-drive pumping unit is optimized. For increasing efficiency and reducing cogging torque, Taguchi's method is employed and height of stator yoke, width of stator tooth, thickness of permanent magnet, and air-gap length are selected as the variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…18 Recently, the orthogonal optimization method has been used as a solution to the multiobjective problem of pump optimization design. Cui et al 19 explored the loss and cogging torque generated during the working process of a permanent magnet synchronous motor. Orthogonal optimization was performed along with FEM analysis for the pumping unit, and the results showed that Taguchi's method was an efficient and effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, the orthogonal optimization method has been used as a solution to the multiobjective problem of pump optimization design. Cui et al 19 explored the loss and cogging torque generated during the working process of a permanent magnet synchronous motor. Orthogonal optimization was performed along with FEM analysis for the pumping unit, and the results showed that Taguchi's method was an efficient and effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows that the downhole direct-drive electric drilling tool powered by a drilling permanent magnet synchronous motor (DPMSM) is the core device in a deepwater subsea coiled tubing drilling rig [7]. Compared with a traditional downhole electric drilling tool, the intermediate reducer is eliminated to realize direct-drive drilling, which reduces the fault point and can effectively improve the reliability of the system; at the same time, permanent magnet synchronous motors (PMSMs) replace electric excitation with the direct excitation of permanent magnets, which avoids excitation loss compared with three-phase asynchronous motors and improves the efficiency of the system [8]. Direct-drive drilling with a PMSM is a new technology.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional beam pumping units are widely used in oilfields due to their advantages of simple structure, high reliability, and convenient maintenance [1][2][3]. However, the structural characteristics of conventional beam pumping units determine their poor balance effect, large net torque fluctuation of the crank output shaft and existence of negative torque, low efficiency, and high energy consumption [4][5][6][7]. The large net torque fluctuation of the crank output shaft and the existence of negative torque are the decisive factors leading to its low efficiency and high energy consumption [8,9].…”
Section: Introductionmentioning
confidence: 99%